Not without our consent : Lakota resistance to termination, 1950-59 - Valandra, Edward Charles, 1955- (Book collections on Project MUSE., 2006)
"In an effort to end the authority of local Native American governments, Congress passed Public Law 83 280 in 1953. Allowing states to apply their criminal and civil laws to Native American country, the law provided an unparalleled opportunity for the state of South Dakota to crush burgeoning Lakota nationalism." "Edward Valandra's Not Without Our Consent documents the tenacious and formidable Lakota opposition to attempts at applying this law. In unprecedented depth, it follows the struggle of the Lakotas through the 1950s when, against all odds, their resistance succeeded in having South Dakota include Native consent as a prerequisite to state jurisdiction. The various House and Senate bills discussed in the book are reproduced in eight appendixes."--Jacket.